Molecular detection and phylogenetic diversity of Staphylococcus aureus isolated from goat subclinical mastitis in Nineveh governorate - Ayman H. Taha; Omar H. Sheet; Dhyaa M. Jwher (Iraqi Journal of Veterinary Sciences)
Mastitis in goats is thought to be caused mainly by Staphylococcus (S.) aureus. On the other hand, little information is known about methicillin-resistant S. aureus (MRSA) in goat milk. The current research aimed to determine the occurrence of S. aureus and MRSA in milk samples from Mosul City's goat farms. Sixty goat milk samples were collected from October 2023 to February 2024 from different governorate areas. This research used conventional techniques such as selective media and biochemical tests. A PCR assay was also used to detect the isolates' nuc, mecA, clfA, clfB, and coa genes. This study showed that the rate of S. aureus in goat subclinical mastitis was 5%, and the high occurrence of S. aureus in goat milk was 20% in the Ali Rash area. In addition, this research revealed that all S. aureus isolates possessed the nuc, mecA, clfB, and coa genes 100% (3/3), while the clfA gene was 66.7% (2/3). There are two types of gene profiles found in S. aureus isolates. Nine novel strains of S. aureus sequences are registered in the NCBI Genbank. The nine newly discovered S. aureus isolates had similarities to other strains of S. aureus found globally. Nine novel strains of S. aureus sequences are registered in the NCBI Genbank. The nine newly discovered S. aureus isolates had similarities to other strains of S. aureus found globally.